Portuguese Consensus on Diagnosis, Treatment, and Management of Anemia in Pediatric Inflammatory Bowel Disease - Lopes,Ana Isabel (2020)
Anemia is a common extraintestinal manifestation of inflammatory bowel disease (IBD), both in pediatric and in adult patients. Iron deficiency is the main cause of anemia in patients with IBD. Anemia is a clinically relevant comorbidity, with impact on patients quality of life and it should be timely diagnosed and adequately treated. Currently, an active treatment approach is the recommended strategy, with evidence showing efficacy and safety of intravenous iron formulations. However, evidence in pediatric age remains scarce and no clinical recommendations exist for the diagnosis and treatment of this particular age group. The present document represents the first national consensus on the management of anemia in pediatric IBD and is therefore particularly relevant. The authors anticipate that the proposed recommendations will be useful in daily clinical practice for diagnosing and managing iron deficiency and iron-deficiency anemia in the pediatric population with IBD.